2012
DOI: 10.2319/080311-488.1
|View full text |Cite
|
Sign up to set email alerts
|

Conventional frontal radiographs compared with frontal radiographs obtained from cone beam computed tomography

Abstract: Aim: To test the hypothesis that there is no difference between measurements performed on conventional frontal radiographs (FRs) and those performed on FRs obtained from cone beam computed tomography (CBCT) scans. Materials and Methods: This study consisted of conventional FRs and CBCT-constructed FRs obtained from 30 young adult patients. Twenty-three landmarks were identified on both types of cephalometric radiographs. Twenty-one widely used cephalometric variables (14 linear distances, 4 angles, and 3 ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…The coefficients of reliability of the pharyngeal airway volume measurements in the present study were above 0.993, agreeing with the findings of previous studies 12,13,16,25,26 using CBCT. Several two-dimensional and 3D studies 8,9,[12][13][14]16,17,[24][25][26] have been performed to evaluate the relationship between airway and sagittal skeletal patterns. It was observed that patients with skeletal Class I and III had significantly larger pharyngeal airway volumes than patients with Class II.…”
Section: Discussionsupporting
confidence: 82%
“…The coefficients of reliability of the pharyngeal airway volume measurements in the present study were above 0.993, agreeing with the findings of previous studies 12,13,16,25,26 using CBCT. Several two-dimensional and 3D studies 8,9,[12][13][14]16,17,[24][25][26] have been performed to evaluate the relationship between airway and sagittal skeletal patterns. It was observed that patients with skeletal Class I and III had significantly larger pharyngeal airway volumes than patients with Class II.…”
Section: Discussionsupporting
confidence: 82%
“…26 The reliability of CBCT method to assess the pharyngeal airway volume and craniofacial measurements was confirmed by several authors. 8,9,14,[26][27][28] In agreement with this finding, the ICC values were above 0.977 for all variables, thus confirming the reliability of those measurements performed on CBCT.…”
Section: Discussionsupporting
confidence: 75%
“…The images were transformed to Digital Imaging and Communications in Medicine (DICOM) format, and then software (Simplant Software, Materialise, Leuven, Belgium) was used to perform the mandibular dental (intercanine and -molar), alveolar (intercanine and -molar), and skeletal (bigonial width) transversal measurements 21,22 (Figures 1-3), which were done at random by an experienced maxillofacial radiologist without knowing the group or sex of the patient. …”
Section: Methodsmentioning
confidence: 99%